Impact of Climate Change and Rubber (Hevea brasiliensis) Plantation Expansion on Reference Evapotranspiration in Xishuangbanna, Southwest China - Ling, Zhen; Shi, Zhengtao; Gu, Shixiang; Wang, Tao; Zhu, Weiwei; Feng, Guojian (Frontiers in Plant Science, 2022)
The expansion of rubber (Hevea brasiliensis) cultivation plantation over the past few decades, has been significant explosive in Xishuangbanna, Southwest of China. More and more evidences concerning the expansion of rubber plantations lead to negative influence to local regional hydrology. It is vital to explore the impact of climate change and rubber (Hevea brasiliensis) plantations expansion on reference evapotranspiration (ETo) for the sustainable and efficient use of regional water resources. In this study, We studied the spatio-temporal variation of ET0 , rubber plantation areas as well as the relationship with them in Xishuangbanna from 1970 to 2017 using trend analysis, correlation analysis and contribution analysis. The results showed that the rubber plantation was 12,768 ha yr-1 from 1990 to 2017 in Xishuangbanna and nearly 40.8% of new rubber plantations expanded above 900 m in altitude from 2000 to 2017. Sunshine duration and average relative humidity were the key meteorological factors affecting ET0 in Xishuangbanna, with the sensitivity coefficient of 0.51 and 0.35, respectively. The multi-year relative change of ET0 in Xishuangbanna was 9.18% and the total contribution of major climate factors was 7.87% during 1970 to 2017. The average relative humidity in the plantation area decreases, which directly leads to the increase of ET0. The amount of ET0 change from 2000 to 2017 affected by climate change increased at 3.13 mm/10a, while it was 2.17 mm/10a affected by the expansion of rubber plantations by quantitative separation. ET0 was significantly affected by climate change but intensified by the expansion of rubber plantation.